2020
DOI: 10.4067/s0718-58392020000300352
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic compounds, antioxidant properties and antifungal activity of jarilla (Barkleyanthus salicifolius ENT#91;KunthENT#93; H. Rob & Brettell)

Abstract: Plant biodiversity provides a natural source of several compounds with biological activity, such as antioxidant and antifungal properties; such effects are related with the concentrations of phenols and flavonoids and different organs of the plants. In this research, aqueous (W) and 70% ethanol (Et70) extracts from flowers (F), leaves (L), stems (S) and roots (R) of Barkleyanthus salicifolius (Kunth) H. Rob. & Brettell were used to test antioxidant and antifungal activities and also the total concentration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…These phenolic acids probably caused damages to the mycelial structure of F. oxysporum, as previously mentioned, and reduced its growth. Other studies have highlighted that phytopathogen inhibition mechanisms vary depending on phenolic compounds and the fungi tested (Nechita et al, 2019;Joaquín-Ramos et al, 2020). In this study, a different trend was observed for Alternaria spp.…”
Section: Antifungal Activity Of Hydrolysatesmentioning
confidence: 52%
See 1 more Smart Citation
“…These phenolic acids probably caused damages to the mycelial structure of F. oxysporum, as previously mentioned, and reduced its growth. Other studies have highlighted that phytopathogen inhibition mechanisms vary depending on phenolic compounds and the fungi tested (Nechita et al, 2019;Joaquín-Ramos et al, 2020). In this study, a different trend was observed for Alternaria spp.…”
Section: Antifungal Activity Of Hydrolysatesmentioning
confidence: 52%
“…Plants produce a huge variety of secondary metabolites that serve to protect them against plant pathogens. In this sense, a high inhibitory effect on F. oxysporum has been reported using plant extracts or formulations based on those extracts (Abd-Elsalam and Khokhlov, 2015;Joaquín-Ramos et al, 2020). Moreover, the potential antifungal activity of different natural formulations to control Alternaria spp.…”
Section: Introductionmentioning
confidence: 99%
“…Other detected polyphenols such as vanillic acid, ferulic acid, catechin, and caffeic acid also have antifungal properties [ 45 ] but they might use an antifungal mechanism other than inhibiting these two fungal enzymes tested in the present study.…”
Section: Discussionmentioning
confidence: 91%
“…Other research has shown that the mechanisms of inhibition of phytopathogens vary depending on the fungus tested, but also depending on the phenolic compounds present in the tested extracts. Thus, the phenolic extract obtained from a mixture of varieties such as 'Cabernet Sauvignon', 'Carmènere' and 'Syrah', subsequently fractionated with hexane, chloroform or ethyl acetate, tested against the phytopathogenic fungus Botrytis cinerea, has a strong fungicidal effect (Joaquín-Ramos et al, 2020).…”
Section: In Vitro Evaluation Of Bio-fungicidesmentioning
confidence: 99%